2020
DOI: 10.21203/rs.3.rs-62420/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Describing variability in pig genes involved in coronavirus infections: towards a One Health perspective in conservation of animal genetic resources

Abstract: Coronaviruses silently circulate in human and animal populations, causing mild to severe diseases. Therefore, livestock are important components of a “One Health” perspective aimed to control these viral infections. However, at present there is no example that considers pig genetic resources in this context. In this study, we investigated the variability of four genes (ACE2, ANPEP and DPP4 encoding for host receptors of the viral spike proteins and TMPRSS2 encoding for a host proteinase) in 23 European (19 aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Single-nucleotide polymorphisms of the APN gene (ANPEP) have been previously described in humans (Vijgen et al, 2004) and pigs (Bovo et al, 2021), and we identified a rare R741G-carrying allele in a heterozygous individual in public databases (STAR Methods), which does not, however, introduce a glycosylation sequon. Moreover, we observed a near-perfect sequence conservation of the CCoV-HuPn-2018 receptor-binding loops with those of TGEV/PRCV, although they are distinct viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphisms of the APN gene (ANPEP) have been previously described in humans (Vijgen et al, 2004) and pigs (Bovo et al, 2021), and we identified a rare R741G-carrying allele in a heterozygous individual in public databases (STAR Methods), which does not, however, introduce a glycosylation sequon. Moreover, we observed a near-perfect sequence conservation of the CCoV-HuPn-2018 receptor-binding loops with those of TGEV/PRCV, although they are distinct viruses.…”
Section: Discussionmentioning
confidence: 99%